# `sqrt(-36)`

*print*Print*list*Cite

### 1 Answer

Since we know

`36=6xx6`

`=6^2`

`i^2=-1`

Therefore

`sqrt(-36)=sqrt(36i^2)`

`=sqrt(6^2i^2)`

`=sqrt((6i)^2)`

`=6i`

*print*Print*list*Cite

Since we know

`36=6xx6`

`=6^2`

`i^2=-1`

Therefore

`sqrt(-36)=sqrt(36i^2)`

`=sqrt(6^2i^2)`

`=sqrt((6i)^2)`

`=6i`

We have a Math tutor online right now to help you!

To chat with a tutor, please set up a tutoring profile by creating an account and setting up a payment method. If you initiate a chat, please note you will be charged $0.50 a minute for tutoring time.